Research on Quasi-isotropic Radiation of Small Circular Arc Antenna - Liu, Hailong; Liu, Jinbo; Nie, Xiaoxia; Song, Jiming; Li, Zengrui (Applied Computational Electromagnetics Society Journal (ACES), 2023)
The radiation characteristics of circular arc antennas are studied by applying the method of moments (MoM) to solve the electric field integral equation (EFIE). Based on the triangular current distribution of small circular arc antennas, the analytical expression of radiation fields of circular arc antennas is derived. It is found that the circular arc antenna is equivalent to a superposition of an electric dipole and a magnetic dipole, resulting in near isotropic radiation pattern. Finally, both MoM and CST simulations show that the small arc antenna can realize the near isotropic radiation pattern.